2016
DOI: 10.3390/buildings6020024
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian Pitched Roof Defects

Abstract: Abstract:The building constructions investigated in this work are pitched wooden roofs with exterior vertical drainpipes and wooden load-bearing system. The aim of this research is to further investigate the building defects of pitched wooden roofs and obtain an overview of typical roof defects. The work involves an analysis of the building defect archive from the research institute SINTEF Building and Infrastructure. The findings from the SINTEF archive show that moisture is a dominant exposure factor, especi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…Even roofs in tropical climates have almost the same type of damage as here in more Nordic regions (Carretero-Ayuso, Moreno-Cansado, & de Brito, 2017). With reference to Gullbrekken, Kvande, Jelle, and Time (2016) and Carretero-Ayuso et al (2017) and their research material, the main roof defects are presented in Table 1.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Even roofs in tropical climates have almost the same type of damage as here in more Nordic regions (Carretero-Ayuso, Moreno-Cansado, & de Brito, 2017). With reference to Gullbrekken, Kvande, Jelle, and Time (2016) and Carretero-Ayuso et al (2017) and their research material, the main roof defects are presented in Table 1.…”
Section: Introductionmentioning
confidence: 93%
“…No matter what the roof is, the factors on the roof can work the same, depending on the climatic conditions (see Table 2). Lars Gullbrekken in his analysis of poor roof defects has highlighted the factors that have the greatest impact on all possible roofs (Gullbrekken et al, 2016). According to him, the critical factor is snow, which accumulates on the roofs, fluctuating in temperature, it melts and freezes again and expands.…”
Section: Introductionmentioning
confidence: 99%
“…Pitched wooden roofs, defined as pitched roofs with a wooden load-bearing structure [1], are traditionally and widely used on small-scale buildings in Nordic countries. The use of wooden roofs poses certain challenges, as building envelopes are subject to large weather strains and related damage risks [2]. To ensure their durability, pitched roofs are designed to be naturally ventilated by allowing air to flow through an air cavity beneath the roofing.…”
Section: Pitched Wooden Roofsmentioning
confidence: 99%
“…Other degradation factors include chemicals (in air pollution, salt spray or bird droppings) and mechanical wear (wind, hail or foot traffic). Gullbrekken et al (2016) conducted research on roof defects in Norway, but with a focus on pitched, ventilated roofs. There appears to be a deficiency of research into the material supply aspect of roof defects.…”
Section: Literature Review Flat Roof Constructionsmentioning
confidence: 99%
“…The roof is usually the most exposed façade of a building, and its protection is crucial to secure the integrity of the rest of the structure. A study by Gullbrekken et al (2016) revealed that roof defects made up 22 % of all building defects investigated by the SINTEF Building and Infrastructure. Out of these were 19 % on compact roofs and 28 % on terraces.…”
Section: Introductionmentioning
confidence: 99%